Relationship Pregnant Women's Weight Gains With The Of Preeclampsia At The Bontobangun Public Health Center - Ely Kurniati; Irmawati; Nabila; Sri Eka Juniarli; Murida Wiryanti; Aldina Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
Pregnancy is very closely related to childbirth, nifas and newborns. The quality of antenatal services provided greatly affects the health of the mother and fetus in the process of childbirth, nifas and newborns. But in its development, every pregnancy has a risk of experiencing complications or complications. Therefore, to ensure the protection of pregnant women and fetuses, efforts are carried out in early detection of risk factors for complications in pregnancy. Preeclampsia is a pregnancy complication characterized by an increase in blood pressure accompanied by proteinuria in pregnant women. Preeclampsia can be bad, even causing death in both the mother and the fetus it contains. This study was observational with a case-control design, where the case group was compared with the control group based on exposure status with a retrospective approach. The research was conducted at the Bontobangun health center, Rilau Ale District, Bulukumba Regency, from August to December 2021. As for the results of the study from 74 respondents, there were 37 normal pregnant women and 37 people the number of pregnant women who had preeclampsia. As for the excess weight gain (high risk) pregnant women who preeclampsia tend to be more than normal pregnant women, namely 6 people who have excess weight gain in pregnant women who are preeclampsia and 1 person who has excess weight gain in normal pregnant women. In addition, all pregnant women experience weight gain in the normal category. The results of the statistical test found that there was a relationship between weight gain and the incidence of preeclampsia at the Bontobangun Kec Health Center, Rilau Ale Kab.Bulukumba Period 2018-2020.